EVALUASI SISTEM E-RESERVASI RAWAT JALAN DENGAN PIECES FRAMEWORK DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM - Diana Safitiri; I Wayan Widi Karsana; Rai Riska Resty Wasita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
The implementation of the e-reservation system at the Regional General Hospital of Mataram has not been maximized due to several obstacles such as errors and long loading times. The purpose of this study is to describe the results of the evaluation of the outpatient e-reservation system at the Mataram Hospital with the PIECES Framework. This type of qualitative research presents the results of interviews and observations conducted by researchers and evaluated with the PIECES Framework. There were 15 informants in this study. The sampling technique used was purposive sampling. The results obtained from this study are the performance of the e-reservation system has produced data according to user needs, makes it easier for users, and still occurs errors, long loading, and failure. Information can already provide accurate, consistent, and relevant information but still get inconsistent information with the services obtained. Economic human resources and supporting resources have supported and helped minimize hospital expenses. Control every employee has access rights and system security is good. Efficiency can already provide convenience in registering through the e-reservation system. The e-reservation system service can already help officers accurately input and output data and reduce waiting time. The conclusion is that the e-reservation system can help users in the service process and facilitate registration so as not to wait long.